1995
DOI: 10.1364/josaa.12.000450
|View full text |Cite
|
Sign up to set email alerts
|

Spectral bandwidth and ocular accommodation

Abstract: Previous studies have suggested that targets illuminated by monochromatic (narrow-band) light are less effective in stimulating the eye to change its focus than are black-white (broadband) targets. The present study investigates the influence of target spectral bandwidth on the dynamic accommodation response in eight subjects. The fixation target was a 3.5-cycle/deg square-wave grating illuminated by midspectral light of various bandwidths [10, 40, and 80 nm and white (CIE Illuminant B)]. The target was moved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 28 publications
5
27
1
Order By: Relevance
“…But it is reasonable to speculate that in white light, some or all of these subjects use optical vergence to compute differences in the amount of defocus between long-, medium-, and short-wavelength-sensitive cone photoreceptors. 35,37,38 The gain values obtained for the open-loop vergence-driven condition were not systematically greater or smaller than for the normal closed-loop condition with feedback and without correcting any aberrations, as in the preliminary experiment. However, subjects generally showed greater temporal lag in the open-loop condition than in the closed-loop condition of the preliminary experiment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…But it is reasonable to speculate that in white light, some or all of these subjects use optical vergence to compute differences in the amount of defocus between long-, medium-, and short-wavelength-sensitive cone photoreceptors. 35,37,38 The gain values obtained for the open-loop vergence-driven condition were not systematically greater or smaller than for the normal closed-loop condition with feedback and without correcting any aberrations, as in the preliminary experiment. However, subjects generally showed greater temporal lag in the open-loop condition than in the closed-loop condition of the preliminary experiment.…”
Section: Discussionsupporting
confidence: 56%
“…33 The 2-D midpoint was chosen because it is an intermediate distance (50 cm in an emmetropic or corrected eye), it is not too large an accommodative demand and so allows measurement in middle-aged subjects, and it is large enough to prevent the accommodative response from reaching 0 D. The majority of previous studies on dynamic accommodation have also used 2 D as the midpoint of accommodative demand, 28,34,35 so the results are directly comparable.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with Troelstra et al [11] who found that spherical and chromatic aberrations were not important to determine the initial direction of accommodation. In contrast, Aggarwala and colleagues [21,22] found that accommodation under monochromatic conditions was not as accurate as accommodation under chromatic conditions which indicates the importance of CA as a cue for accommodation. The difference in our findings could be due to the use of step rather than oscillatory stimuli, as used by Aggarwala et al [21], since the stationary target stimulates voluntary accommodation.…”
Section: Discussionmentioning
confidence: 85%
“…The measurement was completed in both polychromatic and monochromatic light (589 nm). Monochromatic light was used to eliminate CA as a directional clue to accommodation [21,22].…”
Section: Part Twomentioning
confidence: 99%
See 1 more Smart Citation